Preparation method of an intrinsic metal defect catalyst and application of polyphotocatalytic methane dry reforming

By preparing intrinsic metal defect catalysts, the problems of high energy consumption and high pollution in the traditional synthesis gas preparation process are solved, and efficient catalytic methane dry reforming reaction under low temperature conditions is achieved, which significantly improves the catalytic reaction performance and conforms to the trend of green chemical industry.

CN119075997BActive Publication Date: 2025-01-24SOUTHWEST PETROLEUM UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411563010.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-24
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The traditional synthesis gas preparation process has problems of high energy consumption, high pollution and high carbon footprint, and the irreversible sintering of metal oxides under high temperature catalytic conditions leads to catalyst failure.

Method used

The preparation method of this metal defect catalyst is adopted, and the zinc oxide powder rich in metal zinc defective is made by mixing components such as acetate solution with nickel nitrate solution and nickel nitrate solution, and dry, burned, and cooling under vacuum conditions. catalyst. This catalyst is used to catalyze the reaction of methane dry reorganization under concentration conditions.

Benefits of technology

The transformation of high -efficiency catalytic methane and carbon dioxide into synthetic gas under low temperature conditions, significantly improved the catalytic response performance, avoided the problem of failure of high temperature catalysts, and met the requirements of low environmental friendship and cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119075997B_ABST
    Figure CN119075997B_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of catalytic material preparation, and in particular to a method for preparing an intrinsic metal defect catalyst and its application in polyphotocatalytic methane dry reforming. The method comprises the following steps: A, adjusting the pH value of a zinc acetate solution to 5-9, adding glycerol, heating and stirring until a suspension appears, then heating the suspension for reaction, centrifuging, drying, calcining and cooling to obtain a zinc oxide powder rich in metal zinc defects; B, ultrasonically mixing a nickel nitrate aqueous solution, an activator and ascorbic acid to obtain a first mixed solution; C, taking the zinc oxide powder rich in metal zinc defects obtained in step A, adding the first mixed solution obtained in step B and ascorbic acid to the powder to obtain a second mixed solution; D, drying, calcining and cooling the second mixed solution obtained in step C under vacuum conditions to obtain an intrinsic metal defect catalyst. The Ni / Zn(v)O catalyst with intrinsic Zn defects provided by the invention significantly improves light response performance and promotes catalytic efficiency.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of catalytic material preparation, and in particular to a method for preparing an intrinsic metal defect catalyst and its application in polyphotocatalytic methane dry reforming. Background Art

[0002] Syngas is known as the "universal adhesive" of modern industry, and its components are hydrogen and carbon monoxide. In industry, syngas is a key raw material for the production of hydrogen energy, ammonia, methanol, glacial acetic acid and liquid hydrocarbons, and is further used to manufacture high value-added chemicals such as fertilizers, explosives, plastics, synthetic fibers, diesel, naphtha and wax. In recent years, the annual growth rate of the global syngas market will exceed 10%. However, the traditional syngas preparation process uses coal and natural gas as raw materials and is obtained through a high-temperature catalytic route, which has problems such as high energy consumption, high pollution and high carbon footprint. In order to respond to and promote the goal of carbon neutrality, the process of using captured greenhouse gases methane and carbon dioxide as raw materials and using solar energy as an energy source to achieve syngas generation is not only of great strategic significance, but also has a practical effect on solving the energy crisis and environmental pollution.

[0003] As a ubiquitous and renewable green energy source, solar energy can utilize the thermal and photo effects of solar energy. The efficiency of a single photocatalytic reaction is extremely low, which makes it impossible to achieve industrial application. In recent years, the use of concentrated solar catalytic technology can simultaneously achieve the rapid superposition of photo and thermal effects, significantly improve the catalytic efficiency, and is expected to be applied on a large scale in the future. Therefore, it can be used in reactions involving the activation of methane molecules with regular tetrahedral structures and carbon dioxide molecules containing linear symmetry (carbon-oxygen double bonds) and the preparation of synthesis gas. In addition, in order to overcome the irreversible high-temperature sintering phenomenon of metal oxides under high-temperature catalytic conditions (greater than 700°C), the problem of catalyst failure will occur. It is necessary to drive the reaction under low-temperature conditions, which requires that the photo effect rather than the thermal effect should be better utilized to regulate the reaction kinetics under low-temperature concentrated light conditions, so as to effectively improve the catalytic reaction performance in the coupling thermal and photo effect processes. Summary of the invention

[0004] In order to solve the above technical problems, embodiments of the present invention provide a method for preparing an intrinsic metal defect catalyst and its application in polyphotocatalytic methane dry reforming.

[0005] To achieve the above object, the embodiments of the present invention adopt the following technical solutions:

[0006] In one aspect, the present invention provides a method for preparing an intrinsic metal defect catalyst, comprising the following steps:

[0007] A. Adjust the pH value of zinc acetate solution to 5-9, add glycerol, heat and stir until a suspension appears, then heat the suspension for reaction, centrifuge, dry, calcine and cool to obtain zinc oxide powder rich in metal zinc defects;

[0008] B. Ultrasonic mixing the nickel nitrate aqueous solution, the active agent and ascorbic acid to obtain a first mixed solution; this step ensures that the components in the solution are evenly distributed to prevent oxidation during the mixing process;

[0009] C. Take the zinc oxide powder rich in metallic zinc defects obtained in step A, add the first mixed solution obtained in step B and ascorbic acid to obtain a second mixed solution; this step is performed by uniformly dispersing and fixing nickel on the surface of the zinc oxide containing zinc defects and preventing it from being oxidized;

[0010] D. Drying, calcining and cooling the second mixed solution obtained in step C under vacuum conditions to obtain an intrinsic metal defect catalyst. This step removes the residual solvent and enhances the interaction between nickel and zinc oxide.

[0011] In some embodiments, in step A, the zinc acetate solution is obtained by the following method: ethanol, ultrapure water and zinc acetate are mixed to obtain the zinc acetate solution.

[0012] In some embodiments, the molar concentration of the zinc acetate solution is 0.5 mmol / L to 70 mmol / L.

[0013] In some embodiments, in step A, the heating and stirring temperature is 150°C to 250°C, the heating reaction temperature is 100°C to 200°C, the reaction time is 5 to 6 hours, the drying temperature is 150°C to 180°C, the calcination temperature is 300°C to 400°C, and the heating rate is 1°C min ~1 .

[0014] In some embodiments, in step A, the volume ratio of ethanol to ultrapure water is (3-6):(1-2), and the volume ratio of ethanol to glycerol is (3-6):(6-7).

[0015] In some embodiments, in step B, the nickel nitrate aqueous solution is obtained by mixing nickel nitrate with ultrapure water.

[0016] In some embodiments, the mass ratio of the nickel nitrate to ascorbic acid is (0.05-2):(1-5), and the volume ratio of the ultrapure water to the active agent is (1-6):1.

[0017] In some embodiments, the active agent is composed of polyethylene glycol, ethanol and citric acid, and the volume ratio of polyethylene glycol, ethanol and citric acid is (5~12.5): (5~20): (5~12.5).

[0018] In some embodiments, in step C, the mass ratio of the zinc oxide powder rich in metallic zinc defects to ascorbic acid is 1:(1-5);

[0019] In step D, the drying temperature is -50°C to 0°C, the calcination temperature is 400°C to 600°C, and the heating rate is 1°C min -1 .

[0020] On the other hand, the present invention also provides an intrinsic metal defect catalyst prepared by the above-mentioned preparation method for use in polyphotocatalytic methane dry reforming.

[0021] The application of the intrinsic metal defect catalyst of the present invention in the reaction of preparing synthesis gas by catalyzing methane and carbon dioxide using concentrated solar energy. The specific steps are:

[0022] Catalyst materials are filled in a device that can continuously capture and contain methane molecules and carbon dioxide gas. At the same time, with the help of the temperature control function of the reaction device itself, the catalyst surface temperature is adjusted when the catalyst is directly irradiated by concentrated light and reacts, and the product synthesis gas is generated at the same time. In the concentrated flow phase test system containing gas chromatography, the light intensity of solar concentrated light is 1~60 kilowatts / square meter. In addition, no matter how the concentrated light intensity is adjusted, the thermal effect of the light radiation generated by solar energy will be stabilized at 400℃, so that the catalytic reaction can better utilize the coupled light effect in the process of adjusting the light radiation intensity to promote the catalytic reaction and the conversion and generation of products.

[0023] Due to Ni / Zn (v) The ZnO catalytic material has a significant metal defect structure, which can become a deep energy level defect, that is, it introduces an additional energy level in the band gap of zinc oxide and acts as a trap for electrons or holes, regulates the recombination and migration of carriers, and efficiently improves the light response of concentrated solar energy. At the same time, due to the change in the energy level distribution of zinc oxide semiconductors, it also leads to changes in the transition of electrons and the light absorption process, that is, it optimizes the kinetics of the reaction and can induce the reaction to occur in a favorable elementary step. In addition, the metal nickel structure introduced into the material will act as an electron acceptor, providing a good transmission channel for local electrons near the metal defect, promoting the redistribution and migration of free electrons, and further stabilizing the metal defect structure. Furthermore, the synergistic effect between intrinsic Zn defects and metal nickel can enable the catalyst reaction to occur stably in the oxidation-reduction reaction.

[0024] Compared with the prior art, the present invention has at least the following beneficial effects:

[0025] (1) The catalytic synthesis and catalytic reaction of the present invention are both environmentally friendly and low-cost. Ni / Zn with intrinsic Zn defects is prepared under mild conditions using low-cost zinc acetate and nickel nitrate as precursors. (v) O catalyst. The concentrated photocatalytic technology is used to convert methane and carbon dioxide into synthesis gas under normal pressure. The whole catalytic process consumes almost no non-renewable energy and can convert greenhouse gases, which is fully in line with the development trend of green chemical industry.

[0026] (2) The present invention is a Ni / Zn with intrinsic Zn defects (v) The invention provides a new idea for the catalyst of zinc oxide. The invention regulates the presence of metal defects of zinc oxide by controlling the amount of nickel nitrate introduced, the oxidation-reduction effect of the surfactant and the thermal decomposition temperature, and successfully prepares zinc oxide rich in zinc defects.

[0027] (3) Ni / Zn with intrinsic Zn defect provided by the present invention (v) O catalyst, significantly improves light response performance and promotes catalytic efficiency. The presence of surface disordered structure and zinc defects as part of the active component, while modifying the nickel component to construct a composite material. Optimizing the catalytic material from the electronic structure not only improves the photon response ability, but also significantly promotes the catalytic performance, so that the catalysis of the present invention has a synthesis gas yield that general catalysts do not have. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 The Ni / Zn with intrinsic Zn defect of Example 1 (v) X-ray diffraction pattern of O catalyst;

[0029] Figure 2 The Ni / Zn with intrinsic Zn defect of Example 1 (v) Scanning electron micrograph of O catalyst;

[0030] Figure 3 The Ni / Zn with intrinsic Zn defect of Example 1 (v) Comparison of UV-visible absorption spectra of the Ni / ZnO catalyst and the Ni / ZnO catalyst without metal defects of Comparative Example 1;

[0031] Figure 4 The Ni / Zn with intrinsic Zn defect of Example 1 (v) Comparative spectra of electron paramagnetic resonance of the Ni / ZnO catalyst and the Ni / ZnO catalyst without metal defects of Comparative Example 1;

[0032] Figure 5 The Ni / Zn with intrinsic Zn defect of Example 1 (v) Surface temperature variation of O catalyst under concentrated light illumination and non-light illumination conditions;

[0033] Figure 6 Ni / Zn with intrinsic Zn defect of Example 1 (v) Surface temperature variation of O catalyst under different concentrated light intensities. DETAILED DESCRIPTION

[0034] The following will be combined with the accompanying drawings to clearly and completely describe the technical solutions in some embodiments of the present disclosure. Obviously, the described embodiments are only part of the embodiments of the present disclosure, rather than all the embodiments. Based on the embodiments provided by the present disclosure, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present disclosure.

[0035] Example 1

[0036] (1) 60 mL of ethanol and 20 mL of ultrapure water were uniformly mixed, and then 0.9 mmol of zinc acetate was dispersed in the mixed solution, stirred at room temperature (25°C) for 10 min, the pH was adjusted to 7, 60 mL of propylene glycol solution was added, and stirred at 150°C for 2 h, and then allowed to stand for 6 h until a suspension appeared. The suspension was fully reacted at 120°C for 6 h under microwave-assisted conditions, and then centrifuged twice in a polyethylene glycol solution. The solid after centrifugation was dried at 160°C and then calcined in a tube furnace at 1°C min -1 The temperature was raised from room temperature to 400 °C in a nitrogen atmosphere, kept at this temperature for 4 h, and then cooled to 25 °C at a cooling rate of 20 °C min -1 , and zinc oxide powder rich in metal Zn defects is obtained.

[0037] (2) Weigh 0.05 g of nickel nitrate and 50 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of an active agent, wherein the volume ratio of the active agent to polyethylene glycol, ethanol and citric acid is 12.5:5:12.5, stir evenly, then add 3 g of ascorbic acid, and ultrasonicate for 3 h to prepare solution A.

[0038] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to solution A, and stir at 60 °C until it dissolves. The stirring speed is 1000 r min. -1 Then, 2 g of ascorbic acid was added to obtain a composite solution B.

[0039] (4) Dry solution B under vacuum at -50 °C for 72 h to obtain powder C.

[0040] (5) Powder C obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1Heat to 400℃ and keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , Ni / Zn with intrinsic Zn defect can be obtained (v) O catalyst.

[0041] (6) Fill 0.1g Ni / Zn in a device that can continuously capture and contain methane molecules and carbon dioxide gas (v) O catalyst. In the concentrated flow phase test system, the light intensity is 30 kW / m2, and the thermal effect generated by light irradiation will be stabilized at 400°C. At the same time, the reaction gas and production gas are analyzed by gas chromatography (Shimadzu GC-8A) equipped with a thermal conductivity detector (TCD) and a hydrogen ion flame detector (FID). The generated product synthesis gas is detected. The volume ratio of methane and carbon dioxide is 1:1, and the flow rate of the reaction gas (CH4:CO2) is controlled at 30 mL min -1 .

[0042] (7) In order to study the catalytic stability of the catalyst, the Ni / Zn (v) O was subjected to a stability test for a total of 60 h, with sampling every 15 hours. The experimental results are shown in Table 1. The results show that the catalyst can maintain a good catalytic effect during the cyclic test.

[0043]

[0044] Example 2

[0045] Example 2 is the same as Example 1, except that the volume ratio between polyethylene glycol, ethanol and citric acid is 1:1:1.

[0046] Example 3

[0047] Example 3 is the same as Example 1, except that the volume ratio between polyethylene glycol, ethanol and citric acid is 2:3:1.

[0048] Example 4

[0049] Example 4 is the same as Example 1, except that the volume ratio between polyethylene glycol, ethanol and citric acid is 1:4:1.

[0050] In Example 1 to Example 4, the volume ratio of polyethylene glycol, ethanol and citric acid was adjusted, and the effect on the catalytic activity is shown in Table 2. The results show that the best catalytic activity can be obtained when the volume ratio of polyethylene glycol, ethanol and citric acid is 2:3:1.

[0051]

[0052] Example 5

[0053] Example 5 is the same as Example 1, except that 0.2 g of nickel nitrate is used in step (2).

[0054] Example 6

[0055] Example 6 is the same as Example 1, except that 0.4 g of nickel nitrate is used in step (2).

[0056] Example 7

[0057] Example 7 is the same as Example 1, except that in step (2), 0.8 g of nickel nitrate is used.

[0058] Example 8

[0059] Example 8 is the same as Example 1, except that 1.5 g of nickel nitrate is used in step (2).

[0060] Example 1, Example 5 to Example 8 By changing the amount of nickel nitrate, catalysts with different nickel contents were obtained. The effect of different amounts of nickel nitrate on the reaction activity is shown in Table 3. Increasing the content of active component Ni increases the reaction activity accordingly;

[0061]

[0062] Example 9

[0063] Example 9 is the same as Example 1, except that the temperature in the tube furnace in step (5) is 450°C.

[0064] Example 10

[0065] Example 10 is the same as Example 1, except that the temperature in the tube furnace in step (5) is 500°C.

[0066] Embodiment 11

[0067] Example 11 is the same as Example 1, except that the temperature in the tube furnace in step (5) is 550°C.

[0068] Example 12

[0069] Example 12 is the same as Example 1, except that the temperature in the tube furnace in step (5) is 600°C.

[0070] In Example 1, Example 9 to Example 12, by adjusting the temperature in the tubular furnace in step (5), the effect of different calcination temperatures on the catalyst activity is shown in Table 4. As the calcination temperature increases, the reaction activity does not continue to increase, and a performance peak inflection point will appear.

[0071]

[0072] Embodiment 13

[0073] (1) 60 mL of ethanol and 20 mL of ultrapure water were uniformly mixed, 0.9 mmol of zinc acetate was dispersed into the mixed solution, and then stirred at room temperature (25 ° C) for 10 min, the pH was adjusted to 7, 60 mL of propylene glycol solution was added, and stirred at 150 ° C for 2 h, and then allowed to stand for 6 h until a suspension appeared. The suspension was fully reacted at 120 ° C for 6 h under microwave-assisted conditions, and then centrifuged twice in a polyethylene glycol solution. The solid after centrifugation was dried at 160 ° C, and then calcined in a tube furnace at 1 ° C min -1 The heating rate was raised from room temperature to 400 °C in a nitrogen atmosphere, kept at this temperature for 4 h, and then rapidly cooled to 25 °C at a cooling rate of 20 °C min -1 , and obtained four groups of zinc oxide powders rich in different metal Zn defects.

[0074] (2) Weigh 1.5 g of nickel nitrate and 50 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of mixed active agents in different proportions, where the volume ratio of polyethylene glycol, ethanol and citric acid constituting the mixed active agent is 12.5:5:12.5, stir evenly, then add 3 g of ascorbic acid, and ultrasonicate for 3 h to prepare a solution.

[0075] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to the solution in step (2), and stir at high speed at 60°C until it is completely dissolved. The stirring speed is 1000 r min. -1 Then, 2 g of ascorbic acid was added to obtain a solution.

[0076] (4) Dry the solution of step (3) under vacuum at -50°C for 72 h to obtain a powder.

[0077] (5) The powder obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1 Heat to 500℃, keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , we get Ni / Zn with intrinsic Zn defect (v) The O catalyst was named S.

[0078] (6) In a device that can continuously capture and contain methane molecules and carbon dioxide gas, 0.1g of each of the four groups of S catalysts were weighed and four groups of activity tests were set up. In the concentrated flow phase test system, the light intensity was adjusted to 1 kW / m2, 10 kW / m2, 30 kW / m2 and 60 kW / m2 respectively. The thermal effect generated by light irradiation was stabilized at 400°C, and the generated product synthesis gas was detected at the same time. The volume ratio of methane and carbon dioxide was 1:1, and the flow rate of the reaction gas (CH4:CO2) was controlled at 30 mL min -1 .

[0079] (7) The effect of light intensity on catalytic activity is shown in Table 5. For the same catalyst, increasing light intensity leads to increased catalytic activity.

[0080]

[0081] Embodiment 14

[0082] (1) 30 mL of ethanol and 10 mL of ultrapure water were uniformly mixed, and then 0.1 mmol of zinc acetate was dispersed in the mixed solution, stirred at room temperature (25°C) for 5 min, the pH was adjusted to 5, 60 mL of propylene glycol solution was added, and stirred at 150°C for 1 h, and then allowed to stand for 5 h until a suspension appeared. The suspension was fully reacted at 100°C for 5 h under microwave-assisted conditions, and then centrifuged once in a polyethylene glycol solution. The solid after centrifugation was dried at 150°C and then calcined in a tube furnace at 1°C min -1 The temperature was raised from room temperature to 300 °C in a nitrogen atmosphere, kept at this temperature for 3 h, and then cooled to 25 °C at a cooling rate of 20 °C min -1 , and zinc oxide powder rich in metal Zn defects is obtained.

[0083] (2) Weigh 0.05 g of nickel nitrate and 10 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of an active agent, wherein the volume ratio of the active agent to polyethylene glycol, ethanol and citric acid is 1:1:1, stir evenly, then add 1 g of ascorbic acid, and ultrasonicate for 3 h to prepare solution A.

[0084] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to solution A, and stir at 60 °C until it dissolves. The stirring speed is 1000 r min. -1 Then, 1 g of ascorbic acid was added to obtain a composite solution B.

[0085] (4) Dry solution B under vacuum at -50°C for 48 h to obtain powder C.

[0086] (5) Powder C obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1 Heat to 400℃ and keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , Ni / Zn with intrinsic Zn defect can be obtained (v) O catalyst.

[0087] Embodiment 15

[0088] (1) 40 mL of ethanol and 15 mL of ultrapure water were uniformly mixed, and then 1 mmol of zinc acetate was dispersed in the mixed solution. The mixture was stirred at room temperature (25 °C) for 8 min, the pH was adjusted to 7, 65 mL of propylene glycol solution was added, and the mixture was stirred at 180 °C for 2 h, and then allowed to stand for 8 h until a suspension appeared. The suspension was fully reacted at 150 °C for 6 h under microwave-assisted conditions, and then centrifuged twice in a polyethylene glycol solution. The solid after centrifugation was dried at 160 °C and then calcined in a tube furnace at 1 °C min -1 The temperature was raised from room temperature to 350 °C in a nitrogen atmosphere, kept at this temperature for 4 h, and then cooled to 25 °C at a cooling rate of 20 °C min -1 , and zinc oxide powder rich in metal Zn defects is obtained.

[0089] (2) Weigh 0.5 g of nickel nitrate and 20 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of an active agent, wherein the volume ratio of the active agent to polyethylene glycol, ethanol and citric acid is 7:10:11, stir evenly, then add 3 g of ascorbic acid, and ultrasonicate for 3 h to prepare solution A.

[0090] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to solution A, and stir at 60°C until it dissolves. The stirring speed is 1500 r min. -1 Then, 3 g of ascorbic acid was added to obtain a composite solution B.

[0091] (4) Dry solution B under vacuum at -40°C for 72 h to obtain powder C.

[0092] (5) Powder C obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1 Heat to 400℃ and keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , Ni / Zn with intrinsic Zn defect can be obtained (v) O catalyst.

[0093] Example 16

[0094] (1) 50 mL of ethanol and 20 mL of ultrapure water were uniformly mixed, and then 1.8 mmol of zinc acetate was dispersed in the mixed solution, stirred at room temperature (25°C) for 10 min, the pH was adjusted to 8, 65 mL of propylene glycol solution was added, and stirred at 200°C for 2 h, and then allowed to stand for 6 h until a suspension appeared. The suspension was fully reacted at 180°C for 6 h under microwave-assisted conditions, and then centrifuged twice in a polyethylene glycol solution. The solid after centrifugation was dried at 170°C and then calcined in a tube furnace at 1°C min -1 The temperature was raised from room temperature to 400 °C in a nitrogen atmosphere, kept at this temperature for 4 h, and then cooled to 25 °C at a cooling rate of 20 °C min -1 , and zinc oxide powder rich in metal Zn defects is obtained.

[0095] (2) Weigh 1.8 g of nickel nitrate and 50 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of an active agent, wherein the volume ratio of the active agent to polyethylene glycol, ethanol and citric acid is 11:18:12, stir evenly, then add 4 g of ascorbic acid, and ultrasonicate for 3 h to prepare solution A.

[0096] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to solution A, and stir at 60 °C until it dissolves. The stirring speed is 1000 r min. -1 Then, 2 g of ascorbic acid was added to obtain a composite solution B.

[0097] (4) Dry solution B under vacuum at -30°C for 72 h to obtain powder C.

[0098] (5) Powder C obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1 Heat to 500℃ and keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , Ni / Zn with intrinsic Zn defect can be obtained (v) O catalyst.

[0099] Embodiment 17

[0100] (1) 60 mL of ethanol and 20 mL of ultrapure water were uniformly mixed, and then 2.5 mmol of zinc acetate was dispersed in the mixed solution, stirred at room temperature (25°C) for 10 min, the pH was adjusted to 7, 60 mL of propylene glycol solution was added, and stirred at 250°C for 2 h, and then allowed to stand for 10 h until a suspension appeared. The suspension was fully reacted at 180°C for 6 h under microwave-assisted conditions, and then centrifuged three times in a polyethylene glycol solution. The solid after centrifugation was dried at 180°C and then calcined in a tube furnace at 1°C min -1 The temperature was raised from room temperature to 400 °C in a nitrogen atmosphere, kept at this temperature for 4 h, and then cooled to 25 °C at a cooling rate of 20 °C min -1 , and zinc oxide powder rich in metal Zn defects is obtained.

[0101] (2) Weigh 2 g of nickel nitrate and 60 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of an active agent, wherein the volume ratio of the active agent to polyethylene glycol, ethanol and citric acid is 12.5:20:12.5, stir evenly, then add 5 g of ascorbic acid, and ultrasonicate for 3 h to prepare solution A.

[0102] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to solution A, and stir at 100 °C until it dissolves. The stirring speed is 2000 r min. -1 Then, 5 g of ascorbic acid was added to obtain a composite solution B.

[0103] (4) Dry solution B under vacuum at -50 °C for 72 h to obtain powder C.

[0104] (5) Powder C obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1 Heat to 600℃ and keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , Ni / Zn with intrinsic Zn defect can be obtained (v) O catalyst.

[0105] Embodiment 18

[0106] (1) 400 mL of ethanol and 20 mL of ultrapure water were uniformly mixed, and then 2.3 mmol of zinc acetate was dispersed in the mixed solution, stirred at room temperature (25°C) for 10 min, the pH was adjusted to 9, 70 mL of propylene glycol solution was added, and stirred at 250°C for 2 h, and then allowed to stand for 6 h until a suspension appeared. The suspension was fully reacted at 120°C for 6 h under microwave-assisted conditions, and then centrifuged twice in a polyethylene glycol solution. The solid after centrifugation was dried at 160°C and then calcined in a tube furnace at 1°C min -1 The temperature was raised from room temperature to 400 °C in a nitrogen atmosphere, kept at this temperature for 4 h, and then cooled to 25 °C at a cooling rate of 20 °C min -1 , and zinc oxide powder rich in metal Zn defects is obtained.

[0107] (2) Weigh 1 g of nickel nitrate and 50 mL of ultrapure water to prepare a nickel nitrate aqueous solution, then add 10 mL of an active agent, wherein the volume ratio of the active agent to polyethylene glycol, ethanol and citric acid is 6:13:7, stir evenly, then add 3 g of ascorbic acid, and ultrasonicate for 3 h to prepare solution A.

[0108] (3) Weigh 1 g of zinc-deficient zinc oxide powder, add it to solution A, and stir at 60 °C until it dissolves. The stirring speed is 1000 r min. -1 Then, 2 g of ascorbic acid was added to obtain a composite solution B.

[0109] (4) Dry solution B under vacuum at -50 °C for 72 h to obtain powder C.

[0110] (5) Powder C obtained in step (4) was placed in a tubular furnace filled with nitrogen and heated at 1°C min -1 Heat to 400℃ and keep it for 5h, then cool it down to 25℃ and take it out. The cooling rate is 15℃ min -1 , Ni / Zn with intrinsic Zn defect can be obtained (v) O catalyst.

[0111] Comparative Example 1

[0112] (1) Mix 60 mL of ethanol and 20 mL of ultrapure water evenly, then disperse 0.9 mmol of zinc acetate into the mixed solution, stir at room temperature for 10 min, adjust the pH to 7, stir at 150 °C for 2 h, and then let it stand for 6 h until a suspension appears. The suspension is fully reacted at 120 °C for 6 h, then centrifuged in ultrapure water, and the solid after centrifugation is dried at 160 °C, then calcined in a tube furnace at 1 °C min -1The heating rate was raised from room temperature to 400 °C in air atmosphere, kept at this temperature for 4 h, and then rapidly cooled to 25 °C at a cooling rate of 2 °C min -1 , and obtain zinc oxide powder without metal Zn defects.

[0113] (2) Weigh 0.05 g of nickel nitrate and 50 mL of ultrapure water to prepare a nickel nitrate aqueous solution. Stir evenly and perform ultrasonic treatment for 3 h to obtain solution A.

[0114] (3) Weigh 1 g of zinc oxide powder without metal defects, add it to solution A, and stir it at a low speed of 100 r / min at 60°C until it is completely dissolved to obtain a composite solution B.

[0115] (4) Dry solution B under vacuum at -50 °C for 72 h to obtain powder C.

[0116] (5) Powder C obtained in step (4) was placed in a tube furnace in an air atmosphere at 1°C min -1 Heat to 400℃ and keep it for 5h, then cool to 25℃ and take it out, the cooling rate is 2℃ min -1 , the obtained Ni / ZnO catalyst is free of metal defects.

[0117] (6) In a device that can continuously capture and contain methane molecules and carbon dioxide gas, fill 0.1g Ni / ZnO catalyst. In a concentrated flow phase test system, the light intensity is 30 kW / m2, the thermal effect of light irradiation will be stabilized at 400°C, and the generated product synthesis gas will be detected at the same time. The volume ratio of methane and carbon dioxide is 1:1, and the flow rate of the reaction gas (CH4:CO2) is controlled at 30mL min -1 .

[0118] (7) The performance comparison results of Comparative Example 1 and Example 1 under the same reaction conditions are shown in Table 6. The results show that NiZn with intrinsic Zn defects (v) The catalytic effect of the O catalyst for the reaction is better than that of the defect-free Ni / ZnO catalyst.

[0119] Table 6 Comparison of Ni / ZnO catalysts without zinc defects and NiZn with intrinsic Zn defects in Example 1 (v) Performance of O catalysts in the photocatalytic synthesis of syngas

[0120]

[0121] The Ni / Zn with intrinsic Zn defect prepared in Example 1 (v) The catalyst was characterized and the results are as follows:

[0122] (1) Figure 1 The metal defect Ni / Zn prepared in Example 1 (v) X-ray diffraction pattern of O. Analysis Figure 1 It can be seen that the diffraction peaks at 31.8°, 34.4° and 36.3° are the main three strong lines, corresponding to the diffraction peaks of the (100), (002) and (101) crystal planes of the zinc oxide standard card (PDF#99-0111), respectively, indicating that the hexagonal wurtzite structure zinc oxide material was successfully synthesized. Since only 0.05g of nickel nitrate was used in the tested sample, the content was low and it did not cause additional effects on the phase structure, so no other diffraction peaks appeared in the XRD diffraction spectrum. The prepared catalyst material has good crystallinity.

[0123] (2) Figure 2 The metal defect Ni / Zn prepared in Example 1 (v) Scanning electron micrograph of O. Figure 2 It can be seen that the appearance of the catalyst mainly presents a large and thick agglomerate morphology, with a small amount of unevenly dispersed agglomerate flocculent structure. After heat treatment and calcination, the surface of the obtained catalyst is rough, which is related to incomplete crystal growth, grain boundaries, phase boundaries or other crystal defects.

[0124] (3) Figure 3 The metal defect Ni / Zn prepared in Example 1 (v) Comparison of UV-visible absorption spectra of non-metallic defect Ni / ZnO in Example 1 and Comparative Example 1. Figure 3 It can be seen that the Ni / ZnO catalyst without metal defects in Comparative Example 1 has light absorption in the 400nm region; while the Ni / ZnO catalyst rich in metal Zn defects has improved light absorption performance in the ultraviolet-visible light region, which will help to improve the utilization of light effects in the process of concentrated photocatalysis.

[0125] (4) Figure 4 The metal defect Ni / Zn prepared in Example 1 (v) Comparison of the electron paramagnetic resonance spectra of Ni / ZnO and non-metallic defects in Example 1. Figure 4 It can be seen that the Ni / ZnO catalyst of Comparative Example 1 has no EPR signal, indicating that the catalyst surface does not contain any defects. (v) O sample has two sharp electron paramagnetic resonance signals at g values ​​equal to 1.9761 and 1.9313, proving the existence of Zn defects, which indicates that the Ni / Zn(v)O catalytic material with intrinsic Zn defect structure was successfully prepared.

[0126] That is, by attaching Figure 4The metal defects were proved, indicating the presence of deep energy level defects in the material. These defects introduce additional energy levels in the band gap of zinc oxide, acting as traps for electrons or holes. To regulate the recombination and migration of carriers, thereby improving the photoresponsivity of the material. Deep energy level defects can affect the recombination and migration of carriers, which is beneficial to improving the photoresponsivity of concentrated solar energy. In summary, the zinc defects detected in EPR provide evidence support. In addition, UV-light absorption spectra, XRD and SEM all explain the light absorption properties of the material and the defect-related crystal structure. For example, surface roughness is related to incomplete crystal growth, grain boundaries, phase boundaries or other crystal defects.

[0127] (5) Figure 5 The metal defect Ni / Zn prepared in Example 1 (v) Surface temperature variation of O under concentrated irradiation and non-irradiation conditions. Figure 5 It can be seen that under concentrated irradiation conditions, the temperature of the thermal effect generated by light irradiation can be stably controlled at 400°C by means of the catalytic reaction system. Once light irradiation is not introduced into the reaction system, the temperature of the catalyst surface will quickly drop to room temperature. This shows that in the catalytic reaction used in Example 1, light irradiation can indeed produce a thermal effect, but the test system can achieve effective control of solar energy to thermal energy. Therefore, when the catalytic activity test is carried out in Example 1, the light effect can be effectively utilized.

[0128] (6) Figure 6 The metal defect Ni / Zn prepared in Example 1 (v) The surface temperature change of O under concentrated light irradiation is measured by adjusting different light energies. Figure 6 It can be seen that the catalytic reaction system included in the present invention can realize the control of the catalyst surface temperature. When the catalyst of Example 1 is filled in the reaction system, no matter how the concentrated radiation intensity is adjusted, the overall temperature of the reaction system can be stably maintained at 400°C. This also reflects that compared with the traditional heat-driven catalytic reaction process, the intrinsic metal defect Ni / Zn in the present invention (v) O catalysts can more rationally utilize the light efficiency in photothermal reactions.

[0129] In the description of this specification, specific features, structures, materials or characteristics may be combined in an appropriate manner in any one or more embodiments or examples.

[0130] The above is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Any person skilled in the art can easily think of changes or substitutions within the technical scope disclosed by the present invention, which should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A method for preparing an intrinsic metal defect catalyst, characterized in that: The following steps are involved: A. Adjusting the pH value of zinc acetate solution to 5-9, adding glycerol, heating and stirring until a suspension appears, then heating the suspension for reaction, centrifuging, drying, calcining and cooling to obtain zinc oxide powder rich in metal zinc defects; the heating and stirring temperature is 150°C-250°C, the heating reaction temperature is 100°C-200°C, the reaction time is 5-6h, the drying temperature is 150°C-180°C, the calcining temperature is 300°C-400°C, and the heating rate is 1°C min -1 ; B. Ultrasonic mixing of the nickel nitrate aqueous solution, the active agent and ascorbic acid to obtain a first mixed solution; the nickel nitrate aqueous solution is obtained by the following method: mixing nickel nitrate with ultrapure water; The mass ratio of the nickel nitrate to ascorbic acid is (0.05-2):(1-5), and the volume ratio of the ultrapure water to the active agent is (1-6):1; The active agent is composed of polyethylene glycol, ethanol and citric acid, and the volume ratio of the polyethylene glycol, ethanol and citric acid is (5-12.5): (5-20): (5-12.5); C. Take the zinc oxide powder rich in metallic zinc defects obtained in step A, add the first mixed solution obtained in step B and ascorbic acid thereto to obtain a second mixed solution; in step C, the mass ratio of the zinc oxide powder rich in metallic zinc defects to ascorbic acid is 1:(1-5); In step D, the drying temperature is -50°C to 0°C, the calcination temperature is 400°C to 600°C, and the heating rate is 1°C min -1 ; D. Drying, calcining and cooling the second mixed solution obtained in step C under vacuum conditions to obtain an intrinsic metal defect catalyst.

2. The preparation method according to claim 1, characterized in that: In step A, the zinc acetate solution is obtained by the following method: ethanol, ultrapure water and zinc acetate are mixed to obtain the zinc acetate solution.

3. The preparation method according to claim 1, characterized in that: The molar concentration of the zinc acetate solution is 0.5 mmol / L to 70 mmol / L.

4. The preparation method according to claim 2, characterized in that: In step A, the volume ratio of ethanol to ultrapure water is (3-6):(1-2), and the volume ratio of ethanol to glycerol is (3-6):(6-7).

5. Use of an intrinsic metal defect catalyst prepared by the preparation method according to any one of claims 1 to 4 in polyphotocatalytic methane dry reforming.

Citation Information

Patent Citations

  • Low-temperature hydrothermal method for manufacturing zinc oxide nanocrystalline whisker

    CN101220509A

  • Solar condensation catalytic methane dry reforming catalyst as well as preparation method and application thereof

    CN113941334A